The performance of equity portfolio / Nur Farahiah Muhamad Che Ya - Muhamad Che Ya, Nur Farahiah (2017)
Various researches have been done to evaluate the performance of the portfolio. Since the early stage investors and fund manager are lack of knowledge and experience in portfolio construction, this study is conducted to guide them. The purpose of the study are to determine the securities included in the equity portfolio, to identify allocation of each equity and to analyse the performance of the equity portfolio. The data are secondary data that consist of the data from year 2007 to 2016 which consist of the return index (RI) and the beta of the 60 securities listed in Kuala Lumpur composite Index (KLCI) and the FTSE Bursa Malaysia Kuala Lumpur Index Top 100 Index (FBMKLCI 100) which act as the return of the market. All the RI will be calculated to obtain the holding period yield (HPY) of the securities. The discount rate of Malaysia 12-month Treasury bills will be used as the risk free rate. Only the securities that pass Sharpe Single Index Model will be set into the portfolio. The performance of the portfolio will be analysed by using the Treynor and Sharpe Portfolio Performance Measure. The data calculated and evaluated by using Microsoft Office Excel. It was found that only 44 out of 60 securities have sufficient data and four of them pass the Sharpe Simple Index Model. The risk-adjusted performance of portfolio was at the superior. The t-test shows that there is no significance different between the return of the portfolio and the market.